103 Interactions between occupational exposures to extremely low frequency magnetic field and chemicals for brain tumour risk in the INTEROCC study. (11th October 2013) - Turner, C; Benke,; Bowman,; Figuerola-Alquezar,; Fleming,; Hours,; Kincl,; Krewski,; Lavoue,; McLean,; Parent,; Richardson,; et al.
Abstract : Objectives: Brain tumors are a serious, often highly disease with few established risk factors. Although ionizing radiation has been clearly linked with brain tumors, there are a number of other environmental and occupational agents suspected. There may also be interactions between occupational agents for brain tumors however the epidemiological literature is sparse. Only one previous epidemiological study examined potential interactive effects between occupational exposure to extremely low frequency magnetic fields (ELF-MF) and chemical agents with various interactive effects observed. The objective of this paper was to examine the possible joint effects of occupational agents for brain tumors (specifically glioma and meningioma) including occupational ELF-MF and chemicals in the large-scale INTEROCC study. Methods: The INTEROCC study is formed by seven participating countries (Australia, Canada, France, Germany, Israel, New Zealand, United Kingdom) from the parent INTERPHONE study. Cases of primary brain glioma and meningioma aged at least 20 years were recruited between 2000 and 2004. Detailed occupational history data was collected for jobs held at least six months. Job titles were coded into standard international occupational classifications and estimates of ELF-MF and chemical exposure were assigned based on job exposure matrices. Odds ratios (and 95% confidence intervals) for single and joint occupational exposures were calculated according to a common reference category. Interactions on both the additive and multiplicative scale were assessed. Results: Data on a total of 3, 978 brain tumor cases, including 2, 054 gliomas and 1, 924 meningiomas, were analysed with 5, 601 control subjects. A number of interactions were observed, varying according to exposure time window, exposure metric, and included subjects. Results also varied according to tumour type. Conclusion: Interactions between occupational agents for brain tumors were observed however further research examining possible joint effects of occupational agents for brain tumours with refined assessments of occupational exposure in other large-scale studies is warranted.